Risk communication for disaster prevention and management in the rural communities of Mangu local government in Plateau state, Nigeria - Desmond Onyemechi Okocha; Michael Faloseyi; Amaka Cynthia Obiorah (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
Disasters are unpleasant experiences, but disasters are part of the reality of human existence. Human activities have increased the rate, intensity and sources of disasters. Several studies have determined the role of risk communication, an emerging area of communication, in preventing and managing disasters. This study aims to verify the robustness of the claim that risk communication can influence responses in unfavorable situations, thereby reducing the possible consequences of disasters or leading to immediate avoidance. The theoretical framework for this study is the protection motivation theory and the extended parallel process model. Both theories explain how individuals behave when exposed to disaster threats and how risk communication can influence responses in threatening situations. This qualitative research collected data using focus group discussions involving 20 speakers who were purposively selected based on their experience in dealing with disasters in Mangu Local Government Area, Plateau State, Nigeria. This research findings validate risk communication as a proactive approach to reducing the consequences of disasters. The study suggests that government and professional bodies involved in risk communication should invest in capacity building in various skills and needs to earn the trust of their stakeholders to enhance the perceived credibility of their messages.